Foreign Ownership and the Export and Import Propensities of Developing-Country Firms - Dominik Boddin; Horst Raff; Natalia Trofimenko (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper uses micro-data from the World Bank Enterprise Surveys to investigate how foreign ownership affects the likelihood of manufacturers in developing countries to export and/or import both directly and in- directly. Applying propensity score matching to control for differences across firms, we find that foreign ownership raises the propensity of a firm to export by over 17 and the propensity to import by more than 13 percentage points.
Keywords: F12; F14; F23; O19; 330